A daily topical decontamination regimen reduces catheter-related bloodstream infections in haematology patients. Issue 2 (February 2018) - Samuelson, Clare; Kaur, Harpreet; Kritsotakis, Evangelos I.; Goode, Stephen D.; Nield, Aileen; Partridge, David
Summary: Objective: To assess impact of a topical decontamination regimen on rates of catheter-related bloodstream infections (CRBSI) in intensively-treated haematology patients. Methods: A historically-controlled cohort study was used to evaluate the effect of applying chlorhexidine or Octenisan® body washes and nasal Prontoderm® ointment for 5 days around the time of Hickman line insertion on the incidence of CRBSI and infection-free catheter time. Lines inserted during a 24 month period prior to implementation of the decolonisation regimen were compared with those inserted during a 12 month period after the intervention was applied. Results: During the post-intervention period, 163 lines were inserted in 147 patients, compared to 303 lines in 242 patients in the pre-intervention period. CRBSI rates in treated and untreated patients respectively were 6.8 and 35.0 cases per 10, 000 line-days by 21 days (p = 0.009), and 14.4 and 26.0 cases respectively per 10, 000 line-days by 180 days (p = 0.025). The incidence rate of Staphylococcus aureus CRBSI in treated and untreated patients were 0.0 and 4.6 cases per 10, 000 line-days respectively (p = 0.012). Multivariable Cox regression estimated an 81% probability (95% confidence interval 74%–85%) that a treated line develops a CRBSI later than an untreated line by 21 days post-insertion. Conclusion: Implementation of this safe and effective topical decontamination regimen enhances routine CRBSI-prevention measures for haematology patients requiring central venous line insertion. Highlights: A topical decontamination regimen was introduced for haematology patients. Incidence of catheter-related bloodstream infections reduced significantly. Infection-free catheter survival times improved. Staphylococcus aureus infections were particularly reduced.